U-Pb age and Hf isotope composition of detrital zircons from Neoproterozoic sedimentary units in southern Anhui Province, South China: Implications for the provenance, tectonic evolution and glacial history of the eastern Jiangnan Orogen - Cui, X.; Zhu, W.; Fitzsimons, Ian; He, J.; Lu, Y.; Wang, X.; Ge, R.; Zheng, B.; Wu, X. (2015)
Neoproterozoic sedimentary units at the southeastern margin of the Yangtze Block, South China, record a complex geological history including development of the Jiangnan Orogen during assembly of the Yangtze and Cathaysia blocks and later episodes of glacial activity. The timing of these events is controversial, and we have used U-Pb-Hf compositions of detrital zircons from the Lantian type section to constrain their ages in southern Anhui Province, at the eastern end of the Jiangnan Orogen. This section comprises the Xikou Group below an angular unconformity, and the Xiuning Formation and overlying glacial Leigongwu Formation above the unconformity. Detrital zircons in all three units are dominated by 2.6-2.4. Ga, 2.1-1.9. Ga and 960-740. Ma age populations suggesting erosion from similar source regions, and an increasing proportion of older grains up through the sequence reflects a change in depositional environment from syn-collisional to extensional. Pre-Neoproterozoic zircon grains were derived from the Yangtze Block basement, much of which is now concealed by younger rocks, while the Neoproterozoic population was eroded from local igneous rocks in the Jiangnan Orogen. Zircon Hf isotope compositions indicate that 2.6-2.4. Ga source rocks were a mix of juvenile and reworked crust, while 2.1-1.9. Ga source rocks were dominated by reworked crust. Neoproterozoic sources show a switch from 960-860. Ma juvenile crust to 860-740. Ma juvenile and reworked crust, reflecting a transition in the Jiangnan Orogen from subduction to collision and extension. The youngest detrital grains in the Xikou Group and overlying Xiuning Formation indicate deposition after ca. 810. Ma and ca. 732. Ma, respectively, correlating closely with comparable sequences elsewhere in the Yangtze Block. This demonstrates that the unconformity in South Anhui is part of a regional erosion surface that formed more or less synchronously throughout the orogen at 830-800. Ma, consistent with it dating the end of collision between the Yangtze and Cathaysia blocks. The age of the overlying glacial Leigongwu Formation is difficult to constrain from detrital zircons because of a paucity of post-720. Ma source rocks, but our data suggest the Leigongwu diamictite in the Lantian section is a single Marinoan-age glacial unit deposited after 649. ±. 13. Ma. It follows that a carbonate layer in the middle of the Leigongwu diamictite in the Lantian section most likely reflects later faulting, rather than two separate glacial sequences, although we cannot rule out the presence of both Sturtian and Marinoan diamictite elsewhere in South Anhui.